Finite Element Rail Vibration Dynamics - Multi-body Dynamics of Modern High-speed Trains - Ching, Chun Yuen (My University, 2004)
Railway systems have served as a major form of transportation for more than one and a half century. The role of this traditional traffic still remains its importance in spite of by road, water and air traffic. With the advances of technology, trains run faster and faster. Ground vibration problems due to rail vehicle passage have become a concern for the public. Dynamics of rail vehicle is very complicated. Movements of mechanical parts and responses of suspension systems influence the load transferred to the ground. This project is aimed at constructing a multi-body train model for train induced ground borne vibration simulations. The train is modelled in details with car body, bogies, wheels, primary as well as secondary suspension system to obtain realistic load distributions to the rail structure. To analyse different factors concerning ground vibration, three types of high-speed trains: X2000, TGV and ICE are modelled. Results were compared with the early developed box train model . Data obtained suggests maximum amount of vibration occur at about 80m/s. The vibration amplitude is also greatly influenced by the geometry of the train. The movements of the train parts indicate that the train models function as they are supposed to be in the reality. The train models are suitable to be used for studying the effect due to track irregularity, curvature and elevation. It can also be adopted for simulation of ground improvement methods and interaction with other type of structures.
Keywords: Matematik; Samhällsbyggnadsteknik; Teknisk mekanik; Mathematics; Civil Engineering; Applied Mechanics